Primary Segmental Small Bowel Volvulus in an Adolescent Female - Friederike Heidtmann (Georg Thieme Verlag KG, 2021)
Small bowel volvulus is a rare but important cause of abdominal pain and small bowel obstruction in children and adults. In the neonate, small bowel volvulus is a well-known complication of malrotation. Segmental small bowel volvulus is a lesser-known condition, which occurs in children and adults alike and can rapidly progress to bowel ischemia. Primary segmental small bowel volvulus occurs in the absence of rotational anomalies or other intraabdominal lesions and is rare in Europe and North America. Clinical presentation can be misleading, causing a delay in diagnosis and treatment, in which case the resection of necrotic bowel may become necessary. We report on a 14-year-old girl who presented with severe colicky abdominal pain but showed no other signs of peritoneal irritation or bowel obstruction. An emergency magnetic resonance imaging was highly suspicious for small bowel volvulus. Emergency laparotomy revealed a 115 cm segment of strangulated distal ileum with no underlying pathology. We performed a detorsion of the affected bowel segment. Despite the initial markedly ischemic appearance of the affected bowel segment, the patient achieved full recovery without resection of bowel becoming necessary.